Insights into the First Multi-Transition-Metal Containing Ruddlesden Popper-Type Cathode for all-solid-state Fluoride Ion Batteries - Vanita, Vanita; Waidha, Aamir Iqbal; Vasala, Sami; Puphal, Pascal; Schoch, Roland; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver (Journal of Materials Chemistry A)
Promising cathode materials for fluoride-ion batteries (FIBs) are 3d transition metal containing oxides with Ruddlesden-Popper-type structure. So far, multi-elemental compositions were not investigated, but could alternate electrochemical performance similar to what has been found for cathode materials for lithium-ion batteries. Within this study, we investigate RP type La2Ni0.75Co0.25O4.08 as an intercalation-based active cathode material for all-solid-state FIBs. We determine the structural changes of La2Ni0.75Co0.25O4.08 during fluoride intercalation / de-intercalation by ex-situ X-ray diffraction, which showed that F- insertion leads to transformation of the parent phase to three different phases. Changes in Ni and Co oxidation states and coordination environment were examined by X-ray absorption spectroscopy and magnetic measurements in order to understand the complex reaction behaviour of the phases in detail, showing that the two transition metals behave differently in the charging and discharging process. Under optimized operating conditions, a cycle life of 120 cycles at a critical cut-off capacity of 40 mAh g-1 against Pb/PbF2 was obtained, which is one of the highest observed for intercalation electrode materials in FIBs so far. The average Coulombic efficiencies ranged from 85% to 90%. Thus, La2Ni0.75Co0.25O4.08 could be a promising candidate for cycling-stable high-energy cathode materials for all-solid-state FIBs
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

A multi-step framework for the design of a flexible power-to-methane process - Bruns, Bastian; Gross, Michel; Grünewald, Marcus; Bertsch, Valentin; Riese, Julia (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Decentralized production concepts for bio-based polymers - implications for supply chains, costs, and the carbon footprint - Riese, Julia; Fasel, Henrik; Pannok, Maik; Lier, Stefan (Sustainable Production and Consumption)
Keywords: Industrial and Manufacturing Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry; Environmental Engineering

Electrochemical Removal of HF from Carbonate-based LiPF6-containing Li-ion Battery Electrolytes - Ge, Xiaokun; Huck, Marten; Kuhlmann, Andreas; Tiemann, Michael; Weinberger, Christian; Xu, Xiaodan; Zhao, Zhenyu; Steinrueck, Hans-Georg (Journal of The Electrochemical Society)
Due to the hydrolytic instability of LiPF6 in carbonate-based solvents, HF is a typical impurity in Li-ion battery electrolytes. HF significantly influences the performance of Li-ion batteries, for example by impacting the formation of the solid electrolyte interphase at the anode and by affecting transition metal dissolution at the cathode. Additionally, HF complicates studying fundamental interfacial electrochemistry of Li-ion battery electrolytes, such as direct anion reduction, because it is electrocatalytically relatively unstable, resulting in LiF passivation layers. Methods to selectively remove ppm levels of HF from LiPF6-containing carbonate-based electrolytes are limited. We introduce and benchmark a simple yet efficient electrochemical in situ method to selectively remove ppm amounts of HF from LiPF6-containing carbonate-based electrolytes. The basic idea is the application of a suitable potential to a high surface-area metallic electrode upon which only HF reacts (electrocatalytically) while all other electrolyte components are unaffected under the respective conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Geographic Information Systems in Information Systems Research - Review and Research Prospects - Priefer, Jennifer (Proceedings of the 56th Hawaii International Conference on System Sciences)
Since historical times, cartographic maps have revealed spatial relations and enabled decisions and processes. Geographic Information Systems (GIS) allow for acquisition, management, analysis, and presentation of geospatial objects. With free geospatial data becoming available through open data policies and an increasing amount of digitally connected objects in the Internet of Things (IoT), GIS are becoming indispensable to Information Systems (IS) research. However, the consideration and relevance of GIS has only been investigated rarely. We examine, how and in which fields of application GIS have been studied in the IS literature and elicit the importance of GIS regarding their design and usage. A systematic literature review leads us to develop four research propositions. Our results indicate that GIS are still an undeservedly underrepresented discipline in IS and should be more theorized, put center-stage in design-oriented research, and considered for creating superior value co-creation in service systems.
Keywords: GIS; Industry 4.0; and Sustainability; geographic information systems; geospatial data; gis; information systems research; literature review

Characterizing Ion Transport in Electrolytes via Concentration and Velocity Profiles - Mistry, Aashutosh; Srinivasan, Venkat; Steinrück, Hans-Georg (Advanced Energy Materials)
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment

Understanding the Redox Mechanism of Sulfurized Poly(acrylonitrile) as Highly Rate and Cycle Stable Cathode Material for Sodium-Sulfur Batteries - Kappler, Julian; Tonbul, Güldeniz; Schoch, Roland; Murugan, Saravanakumar; Nowakowski, Michał; Lange, Pia Lena; Klostermann, Sina Vanessa; Bauer, Matthias; Schleid, Thomas; Kästner, Johannes; Buchmeiser, Michael Rudolf (Journal of The Electrochemical Society)
Room temperature sodium-sulfur (RT Na-S) batteries are considered potential candidates for stationary power storage applications due to their low cost, broad active material availability and low toxicity. Challenges, such as high volume expansion of the S-cathode upon discharge, low electronic conductivity of S as active material and herewith limited rate capability as well as the shuttling of polysulfides (PSs) as intermediates often impede the cycle stability and practical application of Na-S batteries. Sulfurized poly(acrylonitrile) (SPAN) inherently inhibits the shuttling of PSs and shows compatibility with carbonate-based electrolytes, however, its exact redox mechanism remained unclear to date. Herein, we implement a commercially available and simple electrolyte into the Na-SPAN cell chemistry and demonstrate its high rate and cycle stability. Through the application of in situ techniques utilizing electronic impedance spectroscopy (EIS) and X-ray absorption spectroscopy (XAS) at different depths of charge and discharge, an insight into SPAN’s redox chemistry is obtained.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

Creating water-in-salt-like environment using coordinating anions in non-concentrated aqueous electrolytes for efficient Zn batteries - Gomez Vazquez, Dario; Pollard, Travis P.; Mars, Julian; Yoo, Ji Mun; Steinrück, Hans-Georg; Bone, Sharon E.; Safonova, Olga V.; Toney, Michael F.; Borodin, Oleg; Lukatskaya, Maria R. (Energy & Environmental Science)
By using coordinating anions such as acetate, a water-in-salt-like coordination environment of Zn ions is achieved in relatively dilute conditions, leading to prolonged and efficient cycling of zinc metal anodes.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Break-even of high-temperature heat pump integration for milk spray drying - Schlosser, Florian; Zysk, Sebastian; Walmsley, Timothy G.; Kong, Lana; Zühlsdorf, Benjamin; Meschede, Henning (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Design approach to extend and decarbonise existing district heating systems - case study for German cities - Divkovic, Denis; Knorr, Lukas; Meschede, Henning (International Journal of Sustainable Energy Planning and Management)
This paper aims to present an approach for the planning of carbon low heat supply in a future district heating system based on open data for German cities with existing district heating networks. One focus is on the integration of industrial waste heat and the uncertainty of future waste heat sources as well as restrictions on the use of biomass. For that purpose, knowledge about the energy demand is necessary. In a first step it is shown how the demand around a heating network is estimated with spatial data and a load profile is generated. Local available heat sources are examined according to their suitability and their kind of integration in the heating network. As heat production from different units are optimised, the development of a simulation model will be presented. The simulation is based on the optimisation of the operational costs of the used technologies for heating supply. Different scenarios covering various technologies and economic assumptions are applied. The results show the levelized costs of heating as well as the ecological performance. A sensitivity analysis shows the importance of uncertainties for the economic assumptions. The results showing levelized costs of heating as well as the ecological performance underlining the advantage of excess heat integration.
Keywords: Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Ecological and Economic Feasibility of Inductive Heating for Sustainable Press Hardening Processes - Pfeifer, Florian; Knorr, Lukas; Schlosser, Florian; Marten, Thorsten; Tröster, Thomas (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Handling of uncertainties in the design of sustainable Additive Manufacturing products by merging Design-for-X and Scenario-Technique - Gräßler, Iris; Mozgova, Iryna; Pottebaum, Jens; Ott, Manuel; Jung, Philipp; Hesse, Philipp (Procedia CIRP ICME)
New technologies and materials carry significant potential for sustainable production and use of products. As an example, Additive Manufacturing technologies and materials promise lightweight design and energy efficient use of parts. Exhausting the full potential requires: a) consideration of uncertainties with respect to future capabilities, and b) upgradeable design guidelines to cover advancements consistently. The proposed approach merges concepts of Design-for-X with foresight algorithms of Scenario-Technique to derive actionable knowledge. It is validated by an application in the field of Additive Manufacturing, namely Metal Fused Deposition Modelling. Engineers benefit from the intuitive access to heterogeneous types of sustainability related information.
Keywords: Design-for-X; Scenario-Technique; sustainability; uncertainty; Life-Cycle Engineering; Additive Manufacturing; Circular Economy

Assessment of Energy Efficiency and Flexibility Measures in Electrified Process Heat Generation Based on Simulations in the Animal Feed Industry - Knorr, Lukas; Schlosser, Florian; Meschede, Henning (Journal of Sustainable Development of Energy, Water and Environment Systems)
Keywords: Energy Engineering and Power Technology; Water Science and Technology; Environmental Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Hybrid renewable energy utility systems for industrial sites: A review - Walmsley, Timothy Gordon; Philipp, Matthias; Picón-Núñez, Martín; Meschede, Henning; Taylor, Matthew Thomas; Schlosser, Florian; Atkins, Martin John (Renewable and Sustainable Energy Reviews)
Keywords: Renewable Energy; Sustainability and the Environment

Carbon insetting as a measure to raise supply chain energy efficiency potentials: Opportunities and challenges - Ebersold, Felix; Hechelmann, Ron-Hendrik; Holzapfel, Peter; Meschede, Henning (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Decision support tool to determine the suitability of demand side management implementation in continuously operated processes – A biorefinery case study - Röder, Lilli; Etzold, Hendrik; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract The time‐dependent adjustment of a system's power demand simultaneously with current power generation is commonly referred to as demand side management (DSM). DSM strategies are based on the flexibility to purchase electricity at times when prices are low, which can result in monetary benefits. One option to increase the flexibility of continuously operated processes is to oversize them. From an economic point of view, this leads to an increased investment. DSM only serves an economic purpose if the monetary benefits exceed this increase in capital costs. The main goal of this contribution is to develop a decision support tool to help evaluate unit operations regarding their feasibility for DSM implementation. In a case study, the decision support tool was applied to show its functionality on a biomethane production plant. The results show that with the help of the decision support tool, evaluating unit operations concerning their economic DSM potential is possible.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

CONSIDERING ENGINEERING ACTIVITIES AND PRODUCT CHARACTERISTICS TO ACHIEVE MATERIAL CIRCULARITY BY DESIGN - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Abstract To select design guidelines engineers have to identify relevant from a bewildering amount of design guidelines. In this paper, a rule-based method for selecting design guidelines for material circularity selection is presented. For this purpose, a generic Product Life Cycle model is detailed with regard to Multi Material cycles (gPLC-MM). The presented method is divided into four steps. Core of the presented method is the comparison of circular product strategies with product life phases and material recovery processes. Engineering activities and increments of the product architecture are used to identify design guidelines. The results show that through the material circularity-oriented design guideline identification method, the product architecture is designed for different processes and technologies, to recover materials. The method allows engineers to select guidelines in a more targeted and consolidated way in sustainability-friendly product engineering.
Keywords: Sustainability; Circular economy; Conceptual design

Conformal Pressure and Fast-Charging Li-Ion Batteries - Cao, Chuntian; Steinrück, Hans-Georg; Paul, Partha P; Dunlop, Alison R.; Trask, Stephen E.; Jansen, Andrew; Kasse, Robert M; Thampy, Vivek; Yusuf, Maha; Nelson Weker, Johanna; Shyam, Badri; Subbaraman, Ram; et al. (Journal of The Electrochemical Society)
Abstract Batteries capable of extreme fast-charging (XFC) are a necessity for the deployment of electric vehicles. Material properties of electrodes and electrolytes along with cell parameters such as stack pressure and temperature have coupled, synergistic, and sometimes deleterious effects on fast-charging performance. We develop a new experimental testbed that allows precise and conformal application of electrode stack pressure. We focus on cell capacity degradation using single-layer pouch cells with graphite anodes, LiNi0.5Mn0.3Co0.2O2 (NMC532) cathodes, and carbonate-based electrolyte. In the tested range (10 – 125 psi), cells cycled at higher pressure show higher capacity and less capacity fading. Additionally, Li plating decreases with increasing pressure as observed with scanning electron microscopy (SEM) and optical imaging. While the loss of Li inventory from Li plating is the largest contributor to capacity fade, electrochemical and SEM examination of the NMC cathodes after XFC experiments show increased secondary particle damage at lower pressure. We infer that the better performance at higher pressure is due to more homogenous reactions of active materials across the electrode and less polarization through the electrode thickness. Our study emphasizes the importance of electrode stack pressure in XFC batteries and highlights its subtle role in cell conditions.
Keywords: Materials Chemistry; Electrochemistry; Surfaces; Coatings and Films; Condensed Matter Physics; Renewable Energy; Sustainability and the Environment; Electronic; Optical and Magnetic Materials

A review of 100% renewable energy scenarios on islands - Meschede, Henning; Bertheau, Paul; Khalili, Siavash; Breyer, Christian (WIREs Energy and Environment)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Clear Roads and Dirty Air? Indirect effects of reduced private traffic congestion on emissions from heavy traffic - Hoffmann, Christin; Thommes, Kirsten (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Multimodal quantification of degradation pathways during extreme fast charging of lithium-ion batteries - McShane, Eric J.; Paul, Partha P.; Tanim, Tanvir R.; Cao, Chuntian; Steinrück, Hans-Georg; Thampy, Vivek; Trask, Stephen E.; Dunlop, Alison R.; Jansen, Andrew N.; Dufek, Eric J.; Toney, Michael F.; Weker, Johanna Nelson; et al. (Journal of Materials Chemistry A)
Using a unique combination of advanced characterization techniques, we identify specific degradation mechanisms and quantify degradative species formed during fast charge cycling of lithium-ion battery pouch cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian Joachim; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Who has the future in mind? Gender, time perspectives, and pro-environmental behaviour - Hoffmann, Christin; Hoppe, Julia Amelie; Ziemann, Niklas (Environmental Research Letters)
Abstract An individual’s relation to time may be an important driver of pro-environmental behaviour. We studied whether young individual’s gender and time-orientation are associated with pro-environmental behaviour. In a controlled laboratory environment with students in Germany, participants earned money by performing a real-effort task and were then offered the opportunity to invest their money into an environmental project that supports climate protection. Afterwards, we controlled for their time-orientation. In this consequential behavioural setting, we find that males who scored higher on future-negative orientation showed significantly more pro-environmental behaviour compared to females who scored higher on future-negative orientation and males who scored lower on future-negative orientation. Interestingly, our results are completely reversed when it comes to past-positive orientation. These findings have practical implications regarding the most appropriate way to address individuals in order to achieve more pro-environmental behaviour.
Keywords: Public Health; Environmental and Occupational Health; General Environmental Science; Renewable Energy; Sustainability and the Environment

Experimental Investigation of the Pressure Dependence of Iso-Octane Combustion - Shaqiri, S.; Kaczmarek, D.; vom Lehn, F.; Beeckmann, J.; Pitsch, H.; Kasper, Tina (Frontiers in Energy Research)
Iso-octane is frequently used as a surrogate fuel or as a component in primary reference fuel blends when low-temperature combustion strategies in engines are investigated. To develop control strategies for these engines, the reaction kinetics of iso-octane must be known starting from the low temperatures and intermediate pressures before ignition to the high temperatures and pressures of combustion. This work adds new experimental data sets to the validation data for reaction mechanism development by investigating the oxidation of iso-octane in stoichiometric mixtures in a flow reactor at pressures of p = 1, 10, and 20 bar and 473K ≤ T ≤ 973 K. The experimental data are compared to simulations with recent reaction mechanisms [Atef et al., Combustion and Flame 178, (2017), Bagheri et al., Combustion and Flame 212, (2020), Cai et al., Proceedings of the Combustion Institute 37, (2018), Fang et al., Combustion and Flame 214, (2020)]. The comparison between experimental and simulated mole fractions as function of temperature show reasonable agreement for all investigated pressures. In particular, the experimentally observed onset of low-temperature reactivity above a certain pressure, the shift of the negative temperature coefficient (NTC) regime with increasing pressure to higher temperatures, and the acceleration of the high-temperature chemistry are captured well in the simulations. Deviations between experimental and simulated results are discussed in detail for the reactivity of iso-octane and some key intermediates such as 2,2,4,4-tetramethyl-tetrahydrofuran, iso-butene and acetone at low temperatures.
Keywords: Economics and Econometrics; Energy Engineering and Power Technology; Fuel Technology; Renewable Energy; Sustainability and the Environment

Review of Design-Oriented Green Information Systems Research - Brendel, Alfred Benedikt; Chasin, Friedrich; Mirbabaie, Milad; Riehle, Dennis M.; Harnischmacher, Christine (Sustainability)
Green IS (GIS) research addresses environmental challenges brought on by climate change and the need to preserve the natural environment. Within this scope, design-oriented research, most notably within the Design Science Research (DSR) community, aims to provide solutions to these environmental challenges in the form of novel artifacts. The resulting IS solutions are valuable instruments for reducing emissions, increasing energy efficiency, and mitigating waste. Over the past 14 years, the IS research community was called upon multiple times to focus on designing solutions suitable for facilitating sustainability. However, it is unclear how these calls for action resonated within the design-oriented research community. Against this background, we analyzed the landscape of design-oriented GIS research by looking at 60 different GIS studies that have designed and evaluated an artifact. By analyzing these publications, we were able to make six observations. Based on these observations, we discuss how design-oriented GIS research can evolve to live up to the expectations of creating an immediate positive environmental impact.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Synthesis of Cyclic Carbonates Catalyzed by CaI2–Et3N and Studies on Their Biocatalytic Kinetic Resolution - Terazzi, Constanza; Laatz, Karoline; von Langermann, Jan; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Efficient ethanol electro-reforming on bimetallic anodes supported on adenine-based noble carbons: hydrogen production and value-added chemicals - Rodríguez-Gómez, Alberto; Lepre, Enrico; Dorado, Fernando; Sanchez-Silva, Luz; Lopez Salas, Nieves; de la Osa, Ana Raquel (Materials Today Energy)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Materials Science (miscellaneous); Renewable Energy; Sustainability and the Environment

Overcoming Electron Transfer Efficiency Bottlenecks for Hydrogen Production in Highly Crystalline Carbon Nitride‐Based Materials - Teixeira, Ivo F.; Tarakina, Nadezda V.; Silva, Ingrid F.; Lopez Salas, Nieves; Savateev, Aleksandr; Antonietti, Markus (Advanced Sustainable Systems)
Keywords: General Environmental Science; Renewable Energy; Sustainability and the Environment

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; Lopez Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Ni-based electrocatalysts for unconventional CO2 reduction reaction to formic acid - Lepre, Enrico; Heske, Julian; Nowakowski, Michal; Scoppola, Ernesto; Zizak, Ivo; Heil, Tobias; Kühne, Thomas D.; Antonietti, Markus; López-Salas, Nieves; Albero, Josep (Nano Energy)
Keywords: Electrical and Electronic Engineering; General Materials Science; Renewable Energy; Sustainability and the Environment

Work in Progress: Development of a Virtual and Interactive Microgrids Learning Environment for Microgrids Sustainability – The case of East Africa - Bogere, Paul; Bode, Henrik; Temmen, Katrin (ICL2022 – 25th International Conference on Interactive Collaborative Learning 27–30 September 2022, Hilton Park Vienna, Austria)
Partial coverage of the traditional grid is one of the factors that con-tribute to the low electrical energy access levels in developing countries. This often results in long distances between the grid and unconnected communities. Microgrids, due to their distributed energy resources, have the potential to increase energy access levels. However, there is limited access to microgrids-related knowledge. The knowledge is essential for the effective and efficient use of energy, operation, and hence sustainability of microgrids. To contribute to the sustainability of microgrids, a Virtual and Interactive Microgrids Learning Environment (VIMLE) for microgrids knowledge transfer is developed. VIMLE development is guided by design-based research. With knowledge transfer and skills acquisition through the use of VIMLE, local capacity for designing, installing, operating and maintenance of microgrids is built. Skilled local capacity will contribute to microgrids sustainability. Hence, improve electrical energy access levels and contribute to the achievement of SDG 7.
Keywords: Knowledge Transfer; Microgrids; Sustainability

Following carbon condensation by in situ TEM: towards a rational understanding of the processes in the synthesis of nitrogen-doped carbonaceous materials - Piankova, Diana; Kossmann, Janina; Zschiesche, Hannes; Antonietti, Markus; Lopez Salas, Nieves; Tarakina, Nadezda V. (Journal of Materials Chemistry A)
In situ TEM heating experiments combined with extensive chemical, structural and sorption analysis reveal the nanoscale mechanism of porosity formation in carbonaceous materials obtained directly from molecular precursors.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Modulating between 2e− and 4e− pathways in the oxygen reduction reaction with laser-synthesized iron oxide-grafted nitrogen-doped carbon - Wang, Huize; Jerigova, Maria; Hou, Jing; Tarakina, Nadezda V.; Delacroix, Simon; Lopez Salas, Nieves; Strauss, Volker (Journal of Materials Chemistry A)
Laser patterning of different precursor mixtures allows modulating the selectivity of iron oxide supported on N-doped carbons for ORR electrocatalysis.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Khider Abbas Abbas, Wameedh; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Approach to Sustainability-Based Assessment of Solution Alternatives in Early Stages of Product Engineering - Gräßler, Iris; Hesse, Philipp (Proceedings of the Design Society)
Sustainable product engineering is becoming increasingly important. This includes the development of environmentally friendly products and the design for recycling. In this paper a holistic method for the assessment of solution alternatives is presented, in which the stakeholder perspectives along the generic product lifecycle are taken into account. Finally, a new visualization is presented. By visualizing the results in the integrated sustainability triangle, decision-makers in product development can holistically assess the sustainability of the solution alternatives.
Keywords: sustainability; decision making; generic product lifecycle; design analysis; ecodesign

A mechanistic study of the dopant-induced breakdown in halide perovskites using solid state energy storage devices - Mathieson, Angus G. M.; Dose, Wesley M.; Steinrück, Hans-Georg; Takacs, Christopher J.; Feldmann, Sascha; Pandya, Raj; Merryweather, Alice J.; Mackanic, David; Rao, Akshay; Deschler, Felix; De Volder, Michael (Energy & Environmental Science)
Elucidating and quantifying the effects of doping on halide perovskites using lithium ion batteries.
Keywords: Pollution; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment; Environmental Chemistry

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Abbas, Wameedh Khider Abbas; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Neural Network-Based Demand-Side Management in a Stand-Alone Solar PV-Battery Microgrid Using Load-Shifting and Peak-Clipping - Philipo, Godiana Hagile; Kakande, Josephine Nakato; Krauter, Stefan (Energies)
Due to failures or even the absence of an electricity grid, microgrid systems are becoming popular solutions for electrifying African rural communities. However, they are heavily stressed and complex to control due to their intermittency and demand growth. Demand side management (DSM) serves as an option to increase the level of flexibility on the demand side by scheduling users’ consumption patterns profiles in response to supply. This paper proposes a demand-side management strategy based on load shifting and peak clipping. The proposed approach was modelled in a MATLAB/Simulink R2021a environment and was optimized using the artificial neural network (ANN) algorithm. Simulations were carried out to test the model’s efficacy in a stand-alone PV-battery microgrid in East Africa. The proposed algorithm reduces the peak demand, smoothing the load profile to the desired level, and improves the system’s peak to average ratio (PAR). The presence of deferrable loads has been considered to bring more flexible demand-side management. Results promise decreases in peak demand and peak to average ratio of about 31.2% and 7.5% through peak clipping. In addition, load shifting promises more flexibility to customers.
Keywords: Energy (miscellaneous); Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment; Electrical and Electronic Engineering; Control and Optimization; Engineering (miscellaneous); Building and Construction

Options for demand side management in biofuel production: A systematic review - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Assessing the demand side management potential in biofuel production; A theoretical study for biodiesel, bioethanol, and biomethane in Germany - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (Biofuels, Bioproducts and Biorefining)
Abstract Minimizing the emissions produced during the processing of biofuel, one aim is to reduce or completely replace the amount of the required fossil fuels used for internal process energy. For the transition of process energy from fossil to renewable energy sources, such as solar and wind, the energy demand of biomass processing must be adjustable to the fluctuating electricity supply. The flexible adjustment of a system's power demand to follow the current power generation is commonly referred to as demand side management (DSM). This contribution shows the results of a study on the implementation of DSM in biofuel biorefineries. By identifying reference concepts that could represent biofuel production plants, the specific mass and energy consumption for the individual process steps in these reference concepts was analyzed through a literature study. The annual throughput and energy consumption of process steps in biofuel production could then be calculated, enabling the identification of the most energy‐consuming process steps. Subsequently, possible flexible operating load ranges of the respective process steps in biofuel production were identified. These findings allowed an assessment of the potential for different process units of biorefinery systems concerning the quantitative adaptability of the electricity load – the theoretical DSM potential. An approximate theoretical DSM potential of 146 MW has been identified for biofuel production in Germany. This cumulated theoretical DSM potential in biofuel production was compared to that of other industrial processes, demonstrating the magnitude and importance of the implementation of DSM in biofuel production. © 2022 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.
Keywords: Renewable Energy; Sustainability and the Environment; Bioengineering

Options for demand side management in biofuel production: A systematic review - Röder, Lilli Sophia; Gröngröft, Arne; Grünewald, Marcus; Riese, Julia (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Model-based design of a segmented reactor for the flexible operation of the methanation of CO2 - Herrmann, Felix; Grünewald, Marcus; Riese, Julia (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Improper Signaling for Multicell MIMO RIS-Assisted Broadcast Channels With I/Q Imbalance - Soleymani, Mohammad; Santamaria, Ignacio; Schreier, Peter J. (IEEE Transactions on Green Communications and Networking)
Keywords: Computer Networks and Communications; Renewable Energy; Sustainability and the Environment

A comprehensive framework for sustainable closed-loop supply chain network design - Tavana, Madjid; Kian, Hadi; Nasr, Arash Khalili; Govindan, Kannan; Mina, Hassan (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

A multi-distance interval-valued neutrosophic approach for social failure detection in sustainable municipal waste management - Ebadi Torkayesh, Ali; Tavana, Madjid; Santos-Arteaga, Francisco J. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

SUSTAINABILITY THROUGH THE DIGITALIZATION: EXPLORING POTENTIALS AND DESIGNING VALUE CO-CREATION ARCHITECTURES FOR PRODUCT-SERVICE-SYSTEMS - Scholtysik, Michel; Reinhold, Jannik; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the Design Society)
Digitalization and sustainability are major challenges for today's manufacturing industry. While digitalization is characterized by the incorporation of digital technologies in the products and services as well as the value creation architectures, sustainability requires them to balance economic, environmental and social issues. In both areas, especially Product Service Systems (PSS) are constantly gaining importance. This results in so called smart PSS that integrate digital technologies as well as sustainable PSS which aim at a positive impact on sustainability. Both two concepts cannot be clearly delimited since smart PSS might be designed for sustainability as well and sustainable PSS might be used with digital technologies. This paper aims to investigate the interrelations. To that, digitalization patterns of products and services are evaluated regarding their sustainable impact. The evaluation is conducted by a survey in research and industry. Furthermore, the design of the underlying value creation architecture is investigated. Here, a methodology is proposed enabling companies to optimize their value creation architecture.
Keywords: sustainability

When water becomes an integral part of carbon – combining theory and experiment to understand the zeolite-like water adsorption properties of porous C2N materials - Heske, Julian Joachim; Walczak, Ralf; Epping, Jan D.; Youk, Sol; Sahoo, Sudhir K.; Antonietti, Markus; Kühne, Thomas; Oschatz, Martin (Journal of Materials Chemistry A)
The origin of strong interactions between water molecules and porous C 2 N surfaces is investigated by using a combination of model materials, volumetric physisorption measurements, solid-state NMR spectroscopy, and DFT calculations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

CuII/CuI decorated N-doped carbonaceous electrocatalysts for the oxygen reduction reaction - Kossmann, Janina; Ortíz Sánchez-Manjavacas, María Luz; Zschiesche, Hannes; Tarakina, Nadezda V.; Antonietti, Markus; Albero, Josep; Lopez Salas, Nieves (Journal of Materials Chemistry A)
Copper- and nitrogen-doped carbonaceous materials, obtained by a simple synthetic procedure are highly efficient and fast catalysts for the oxygen reduction reaction. It is shown, that Cu( i ) containing materials perform with faster reaction kinetics.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

A Comparative Analysis of Consumption: Evidence from a Cultural Goods Market - Kaimann, Daniel; Cox, Joe (Sustainability)
This study uniquely employs a fuzzy-set qualitative comparative analysis (fsQCA) technique to account for complex relationships in consumption. The fsQCA technique assumes that relationships are based on a set–subset relationship. This assumption is fundamental when decision-makers are affected by information asymmetry and are, thus, required to jointly evaluate the credibility and reliability of a range of external signals. This issue also affects consumers in markets for cultural goods, where the quality of products is not known with certainty in advance of the purchase decision. Our study uses fsQCA to establish the effect of different quality signals on consumption in the US market for video game software. Our results show that reviews from professional critics alongside brand extension and multi-platform release strategies act as signals of product quality and, therefore, lead to high sales performance.
Keywords: Management; Monitoring; Policy and Law; Renewable Energy; Sustainability and the Environment; Geography; Planning and Development

Cascaded dual-loop organic Rankine cycle with alkanes and low global warming potential refrigerants as working fluids - Abbas, Wameedh Khider Abbas; Vrabec, Jadran (Energy Conversion and Management)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Kinetic studies of cathode degradation on PEM fuel cell short stack level undergoing freeze startups with different states of residual water and current draws - Liphardt, L.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Further Extending the Dilution Range of the “Solvent-in-DES” Regime upon the Replacement of Water by an Organic Solvent with Hydrogen Bond Capabilities - Lopez Salas, Nieves; Vicent-Luna, J. M.; Posada, E.; Imberti, S.; Madero-Castro, R. M.; Calero, S.; Ania, C. O.; Jiménez-Riobóo, R. J.; Gutiérrez, M. C.; Ferrer, M. L.; del Monte, F. (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Synergetic modulation of the electronic structure and hydrophilicity of nickel–iron hydroxide for efficient oxygen evolution by UV/ozone treatment - Pan, Ying; Wu, Yanfang; Hsain, H. Alex; Su, Ran; Cazorla, Claudio; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced OER performance of Ni(Fe) hydroxide through UV/ozone treatment.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Assessment of electrocatalytic activity through the lens of three surface area normalization techniques - Ren, Hangjuan; Pan, Ying; Sorrell, Charles C.; Du, Haiwei (Journal of Materials Chemistry A)
Electrocatalytic activities of electrodes for water splitting are assessed via geometric area, BET surface area and ECSA normalisations.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Polyethers as Complexing Agents in Calcium-Catalyzed Cyclic Carbonate Synthesis - Hu, Yuya; Steinbauer, Johannes; Stefanow, Vivian; Spannenberg, Anke; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Catalytic Systems for the Synthesis of Biscarbonates and Their Impact on the Sequential Preparation of Non-Isocyanate Polyurethanes - Wulf, Christoph; Reckers, Matthias; Perechodjuk, Anna; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Looking at the “Water-in-Deep-Eutectic-Solvent” System: A Dilution Range for High Performance Eutectics - Lopez Salas, Nieves; Vicent-Luna, José Manuel; Imberti, Silvia; Posada, Elena; Roldán, María Jesús; Anta, Juan A.; Balestra, Salvador R. G.; Madero Castro, Rafael M.; Calero, Sofia; Jiménez-Riobóo, Rafael J.; Gutiérrez, María Concepción; Ferrer, María Luisa; et al. (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

The value of signals: Do self-declaration and certification generate price premiums for organic and biodynamic wines? - Fanasch, Patrizia; Frick, Bernd (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Mechanistic Study on the Addition of CO2 to Epoxides Catalyzed by Ammonium and Phosphonium Salts: A Combined Spectroscopic and Kinetic Approach - Steinbauer, Johannes; Kubis, Christoph; Ludwig, Ralf; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Developing intercalation based anode materials for fluoride-ion batteries: topochemical reduction of Sr2TiO3F2via a hydride based defluorination process - Wissel, Kerstin; Dasgupta, Supratik; Benes, Alexander; Schoch, Roland; Bauer, Matthias; Witte, Ralf; Fortes, Andrew Dominic; Erdem, Emre; Rohrer, Jochen; Clemens, Oliver (Journal of Materials Chemistry A)
Sr2TiO3F2−x, a potential anode material for fluoride ion batteries, is prepared in the charged state via selective low-temperature defluorination.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Active site engineering by surface sulfurization for a highly efficient oxygen evolution reaction: a case study of Co3O4 electrocatalysts - Pan, Ying; Ren, Hangjuan; Du, Haiwei; Cao, Fuyang; Jiang, Yifeng; Du, Haojin; Chu, Dewei (Journal of Materials Chemistry A)
Enhanced catalytic activity of Co3O4@CoSx through surface sulfurization.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Political embeddedness and the diffusion of corporate social responsibility practices in China: A trade-off between financial and CSR performance? - Wang, Zhi; Reimsbach, Daniel; Braam, Geert (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment; Building and Construction

Optimization of the energy supply in the plastics industry to reduce the primary energy demand - Dunkelberg, Heiko; Wagner, Johannes; Hannen, Conrad; Schlüter, Alexander; Phan, Long; Hesselbach, Jens; Lin, Cheng-Xian (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Surface Cleaning and Modification by High Intense UV-Irradition for TiO2 Nanoparticle Films in Dye Sensitized Solar Cells - Kleine, A.; Hilleringmann, Ulrich (Renewable Energy and Power Quality Journal)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment

Design and Implementation of a High Temperature Control Monitoring Applied to Micro Thermoelectric Generators - Jucá, S.C.S.; Carvalho, P.C.M.; Pereira, R.I.S.; Petrov, D.; Hilleringmann, Ulrich (Renewable Energy and Power Quality Journal)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment

Increasing the Efficiency of Solar Cells by Combining Silicon- and Dye Sensitized Devices - Ohms, B.; Kleine, A.; Hilleringmann, Ulrich (Renewable Energy and Power Quality)
Keywords: Electrical and Electronic Engineering; Energy Engineering and Power Technology; Renewable Energy; Sustainability and the Environment

An open-data approach for quantifying the potential of taxi ridesharing - Barann, Benjamin; Beverungen, Daniel; Müller, Oliver (Decision Support Systems)
Taxi ridesharing1 (TRS) is an advanced form of urban transportation that matches separate ride requests with similar spatio-temporal characteristics to a jointly used taxi. As collaborative consumption, TRS saves customers money, enables taxi companies to economize use of their resources, and lowers greenhouse gas emissions. We develop a one-to-one TRS approach that matches rides with similar start and end points. We evaluate our approach by analyzing an open dataset of > 5 million taxi trajectories in New York City. Our empirical analysis reveals that the proposed approach matches up to 48.34% of all taxi rides, saving 2,892,036 km of travel distance, 231,362.89 l of gas, and 532,134.64 kg of CO2 emissions per week. Compared to many-to-many TRS approaches, our approach is competitive, simpler to implement and operate, and poses less rigid assumptions on data availability and customer acceptance.
Keywords: Taxi ridesharing Collaborative consumption Transportation Open data Sustainability Shared mobility

Iron-Based Binary Catalytic System for the Valorization of CO2 into Biobased Cyclic Carbonates - Büttner, Hendrik; Grimmer, Christoph; Steinbauer, Johannes; Werner, Thomas (ACS Sustainable Chemistry & Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Tailoring the textural properties of hierarchical porous carbons using deep eutectic solvents - Lopez Salas, Nieves; Carriazo, D.; Gutiérrez, M. C.; Ferrer, M. L.; Ania, C. O.; Rubio, F.; Tamayo, A.; Fierro, J. L. G.; del Monte, F. (Journal of Materials Chemistry A)
DESs containing resorcinol, urea and choline chloride allow the preparation of monolithic carbons with bicontinuous porous structures, the pore dimension of which can be easily tailored by the molar ratio of the components at the original DES.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

A holistic approach to energy efficiency assessment in plastic processing - Schlüter, Alexander; Rosano, Michele B. (Journal of Cleaner Production)
Keywords: Industrial and Manufacturing Engineering; Strategy and Management; General Environmental Science; Renewable Energy; Sustainability and the Environment

Recycling of Phosphorus-Based Organocatalysts by Organic Solvent Nanofiltration - Großeheilmann, Julia; Büttner, Hendrik; Kohrt, Christina; Kragl, Udo; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Phosphorus-doped carbon–carbon nanotube hierarchical monoliths as true three-dimensional electrodes in supercapacitor cells - Patiño, Julián; Lopez Salas, Nieves; Gutiérrez, María C.; Carriazo, Daniel; Ferrer, M. Luisa; Monte, Francisco del (Journal of Materials Chemistry A)
Phosphorus-doped carbon–carbon nanotube hierarchical monoliths exhibiting energy densities of around 22.6 W h kg−1 at power densities of up to 10 kW kg−1 were capable of functioning as true three-dimensional electrodes in supercapacitor cells.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Nitrogen-doped carbons prepared from eutectic mixtures as metal-free oxygen reduction catalysts - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Muñoz-Márquez, Miguel A.; Luisa Ferrer, M.; Monte, Francisco del (Journal of Materials Chemistry A)
Deep eutectic solvents (DESs) composed of resorcinol, either 2-cyanophenol or 4-cyanophenol, and choline chloride were used for the synthesis of hierarchical nitrogen-doped carbon molecular sieves.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

Efficient nitrogen-doping and structural control of hierarchical carbons using unconventional precursors in the form of deep eutectic solvents - Lopez Salas, Nieves; Gutiérrez, María C.; Ania, Conchi O.; Fierro, José Luís G.; Luisa Ferrer, M.; Monte, Francisco del (J. Mater. Chem. A)
Deep eutectic solvents formed with unconventional carbon precursors were used for the preparation of hierarchical carbon monoliths and proved effective for doping the resulting carbons with nitrogen.
Keywords: General Materials Science; Renewable Energy; Sustainability and the Environment; General Chemistry

External governance outcome and microfinance success - Uhde, André; Müller, Oliver (International Journal of Monetary Economics and Finance)
Employing a Hausman–Taylor instrument variable (HT–IV) estimator to data from 558 microfinance institutions (MFIs) in 80 developing countries for the period from 2002 to 2007, this paper provides empirical evidence for a positive impact of a country's external governance quality and outcome on local microbanks' economic success in terms of profitability and sustainability. Evidence as well suggests a negative relationship between external governance and the microbanks' social success measured by the depth of outreach. In this context, our analysis reveals that a country's political stability, governance effectiveness, regulatory quality and rule of law are significant key elements of external governance affecting the MFIs' functional performance. Moreover, results from sensitivity analyses indicate that the relationship between external governance quality and microfinance functional performance significantly depends on the microbanks' business concepts, their lending methodologies and sources of funding.
Keywords: microfinance; external governance; economic success; social success; developing countries; profitability; sustainability; microbanks; outreach; political stability; governance effectiveness; regulatory quality; rule of law; governance quality; lending methodologies; funding sources

Enhanced organic light-emitting diode based on a columnar liquid crystal by integration in a microresonator - Kasdorf, Olga; Vollbrecht, Joachim; Ohms, Benjamin; Hilleringmann, Ulrich; Bock, Harald; Kitzerow, Heinz-S. (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Enhanced organic light-emitting diode based on a columnar liquid crystal by integration in a microresonator - Kasdorf, Olga; Vollbrecht, Joachim; Ohms, Benjamin; Hilleringmann, Ulrich; Bock, Harald; Kitzerow, Heinz-Siegfried (International Journal of Energy Research)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment